Two new species of Platynothrus and Heminothrus (Oribatida: Crotoniidae) from Mexico - Villagomez, Fernando; Heethoff, Michael (Zootaxa, 2024)
The oribatid mite genera Platynothrus and Heminothrus currently comprise 20 and 10 species, respectively, and collectively have a cosmopolitan distribution. They have been classified into three to five subgenera, depending on the classification. For Platynothrus, a couple of new species have been described in the last two years, while for Heminothrus, the last formal description of a new species was 26 years ago. In this study, we describe two new species of these crotoniid mites, discovered in the soil and litter of a tropical montane cloud forest in Mexico. One of these new species belongs to the genus Platynothrus, which can be distinguished from other species of this genus by the short clavate sensillus, curved smooth interlamellar seta, and the length of the notogastral setae. The second new species belongs to the genus Heminothrus, being characterized by a short rhomboidal sensillus and a very long interlamellar seta. Intraspecific genetic distances of the COX-1 mitochondrial marker were 2.15%, and 0.81% for the new Platynothrus and Heminothrus species, respectively.